Diabesity and mood disorders: Multiple links through the microbiota-gut-brain axis. (April 2019) - Farzi, Aitak; Hassan, Ahmed M.; Zenz, Geraldine; Holzer, Peter
Abstract: The global prevalence of diabesity is on the rise, and the clinical, social and economic health burden arising from this epidemic is aggravated by a significant co-morbidity of diabesity with neuropsychiatric disease, particularly depression. Importantly, not only is the prevalence of mood disorders elevated in patients with type 2 diabetes, depressed patients are also more prone to develop diabetes. This reciprocal relationship calls for a molecular and systemic analysis of diabesity-brain interactions to guide preventive and therapeutic strategies. The analysis we are presenting in this review is modelled on the microbiota-gut-brain axis, which provides the brain with information from the gut not only via the nervous system, but also via a continuous stream of microbial, endocrine, metabolic and immune messages. This communication network offers important clues as to how obesity and diabetes could target the brain to provoke neuropsychiatric disease. There is emerging evidence that the gut microbiota is orchestrating a multiplicity of bodily functions that are intimately related to the immune, metabolic and nervous systems and that gut dysbiosis spoils the homeostasis between these systems. In our article we highlight two groups of molecular links that seem to have a significant bearing on the impact of diabesity on the brain. On the one hand, we focus on microbiota-related metabolites such as short-chain fatty acids, tryptophan metabolites, immune stimulants and endocannabinoids that are likely to play a mediator role. On the other hand, we discuss signalling molecules that operate primarily in the brain, specifically neuropeptide Y, brain-derived neurotrophic factor and γ-amino butyric acid, that are disturbed by microbial factors, obesity and diabetes and are relevant to mental illness. Finally, we address the usefulness of diet-related interventions to suspend the deleterious relationship between diabesity and mood disorders.